(untitled) (Tri-Chandra Journal of Anthropology, 2025)
This paper aims to assess burnout among nurses in the Critical Care Unit of the National Academy of Medical Sciences -Bir Hospital, explore their coping strategies, and examine the correlation between burnout and coping mechanisms. A cross-sectional descriptive study was conducted among 154 critical care nurses using the Burnout Assessment Tool to evaluate burnout across four dimensions: Emotional Exhaustion, Mental Distance, Cognitive Impairment, and Emotional Impairment. Coping strategies were assessed using a closed-ended questionnaire covering fourteen dimensions. The overall burnout level was high, with a score of 2.55. Factors associated with higher burnout levels included urban residency, ethnicity, higher designation, level of education, marital status, number of dependents, and longer work experience in the CCU. Significant relationships were found between burnout and the use of coping mechanisms such as humor, self-distraction, denial, substance use, self-blame, and behavioral disengagement. In contrast, there was little to no relationship between burnout and the use of acceptance, planning, active coping, emotional support, positive reframing, venting, spiritual support, and instrumental support. The study underscores the importance of addressing workplace stressors at the organizational level and recommends further in-depth research on the topic across multiple settings.